The Moderating Role of Work Context in Job Design Research: A Test of Competing Models - Ferris, Gerald R.; Gilmore, Davìd C. (Academy of Management Journal, 1984)
The article discusses a study which tested the moderating effects of organizational climate on the relationship between job complexity and job satisfaction. Data was collected from nursing service employees who were employed in a skilled nursing care facility operated by a county government. The potential moderating effects of organizational climate were examined using moderated regression analysis. The study further examined subgroup correlations and slopes to determine both the form and degree of the job complexity–job relationship effect at different levels of the organizational climate.